Pengaruh Managerial Ownership, Profitability, Firm Size dan Capital Structure - Dimas Wicaksono; Ade Saputra (AKRUAL : Jurnal Akuntansi dan Keuangan, 2023)
This study aims to examine the effect of the variables Managerial Ownership, Profitability, and Company Size on Capital Structure in Food and Beverage Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2021 period. In this study, capital structure is measured using the Debt to Equity Ratio (DER). Samples were taken by purposive sampling method with certain criteria, during the study period. Based on the predetermined sample criteria, the number of observational data that can be processed is 60 data. The analytical method used is Multiple Linear Regression processed using SPSS 25. The results of this study indicate that the independent variable Managerial Ownership has a negative and significant effect on the dependent variable Capital Structure. Profitability independent variable has a negative and significant effect on the dependent variable Capital Structure. While the independent variable Firm Size has a positive and significant effect on the dependent variable Capital Structure.